A randomized open-label study of sodium valproate vs sumatriptan and metoclopramide for prolonged migraine headache - Bakhshayesh, Babak; Seyed Saadat, Seyed Mohammad; Rezania, Kourosh; Hatamian, Hamidreza; Hossieninezhad, Mozaffar (The American journal of emergency medicine, 2013)
The objective of this study is to compare the efficacy and tolerability of intravenous valproic acid (iVPA) with intramuscular metoclopramide + subcutaneous (SQ) sumatriptan for prolonged acute migraine. Intravenous valproic acid has been explored as a possible treatment of acute migraine. Sumatriptan and newer generation triptans are also effective for migraine. However, iVPA has not yet been compared with triptans in head-to-head studies. Patients presenting with moderate to severe intensity migraine without aura were randomized to receive either 400 mg of iVPA or 10 mg intramuscular metoclopramide + 6 mg SQ sumatriptan (30 patients in each study arm). The severity of headache and other associated symptoms such as photophobia and phonophobia were assessed at baseline and after 20 minutes and 1, 2, 4, and 24 hours. The primary end point was to compare the efficacy of the 2 study treatments in relieving headache from moderate-severe to none-mild and of other associated symptoms within a period of 24 hours. Pain relief from severe or moderate to mild or none was obtained in 53.3% of subjects in the iVPA arm and 23.3% in the metoclopramide + sumatriptan arm at 1 hour following treatment (P = .033), whereas 60% and 30% reported pain relief at 2 hour (P = .037). There was no other significant difference in alleviation of associated migraine symptoms between the 2 arms. No serious adverse effects were noted. Treatment with iVPA was more effective than metoclopramide + SQ sumatriptan during the first 2 hours in patients with a prolonged migraine.